Optimal Control for Minimum-Fuel Geostationary Station Keeping of Satellites Equipped with Electric Propulsion. Issue 17 (2016) - Gazzino, C.; Arzelier, D.; Losa, D.; Louembet, C.; Pittet, C.; Cerri, L.
Abstract: In this paper, a control scheme is elaborated to perform the station keeping of a geostationary satellite equipped with electric propulsion. The use of electric thrusters imposes to take into account some additional non linear constraints that make the overall station keeping optimal control problem difficult to solve directly. That is why we choose here to decompose the station keeping problem in two control problems. The first one consists in solving a classical optimal control problem with an indirect method initialized by a direct method without using the thrusters operational constraints. The second problem deals with the thrusters operating constraints, that are taken into account by two different ways. Simulation results validate the effect of the optimal control thrusts obtained with these methods.